Mobilization of Calcium from Intracellular Stores Facilitates Somatodendritic Dopamine Release - Patel, Jyoti C. (Society for Neuroscience, 2009)
Somatodendritic dopamine (DA) release in the substantia nigra pars compacta (SNc) shows a limited dependence on extracellular calcium concentration ([Ca(2+)](o)), suggesting the involvement of intracellular Ca(2+) stores. Here, using immunocytochemistry we demonstrate the presence of the sarcoplasmic/endoplasmic reticulum Ca(2+)-ATPase 2 (SERCA2) that sequesters cytosolic Ca(2+) into the endoplasmic reticulum (ER), as well as inositol 1,4,5-triphosphate receptors (IP(3)Rs) and ryanodine receptors (RyRs) in DAergic neurons. Notably, RyRs were clustered at the plasma membrane, poised for activation by Ca(2+) entry. Using fast-scan cyclic voltammetry to monitor evoked extracellular DA concentration ([DA](o)) in midbrain slices, we found that SERCA inhibition by cyclopiazonic acid (CPA) decreased evoked [DA](o) in the SNc, indicating a functional role for ER Ca(2+) stores in somatodendritic DA release. Implicating IP(3)R-dependent stores, an IP(3)R antagonist, 2-APB, also decreased evoked [DA](o). Moreover, DHPG, an agonist of group I metabotropic glutamate receptors (mGluR1s, which couple to IP(3) production), increased somatodendritic DA release, whereas CPCCOEt, an mGluR1 antagonist, suppressed it. Release suppression by mGluR1 blockade was prevented by 2-APB or CPA, indicating facilitation of DA release by endogenous glutamate acting via mGluR1s and IP(3)R-gated Ca(2+) stores. Similarly, activation of RyRs by caffeine increased [Ca(2+)](i) and elevated evoked [DA](o). The increase in DA release was prevented by a RyR blocker, dantrolene, and by CPA. Importantly, the efficacy of dantrolene was enhanced in low [Ca(2+)](o), suggesting a mechanism for maintenance of somatodendritic DA release with limited Ca(2+) entry. Thus, both mGluR1-linked IP(3)R- and RyR-dependent ER Ca(2+) stores facilitate somatodendritic DA release in the SNc.